Three-degree-of-freedom positioning control of magnetically levitated permanent magnet planar motor using active disturbance rejection control scheme. (July 2017) - Zhang, Xinhua; Zhu, Qing; Sun, Yukun; Yang, Zebin; Sun, Xiaodong
Magnetically levitated permanent magnet planar motor is a new-generation motion device in modern precision industry, and the design of advanced motion controller has always been a main concern in the research and development of magnetically levitated permanent magnet planar motor. Due to the decrease in electromagnetic force caused by the deflection of the mover or the sharp decrease in magnetic flux density with height, it is very difficult to realize accurate positioning control of 3 degrees of freedom. In this article, an active disturbance rejection control scheme is adopted. The extended state observer is used to estimate the comprehensive disturbance and motion state in real time. Then, according to the value estimated by the extended state observer, the active disturbance rejection control motion controller can compensate the electromagnetic force in time to achieve good anti-jamming performance. Simulation and experimental results demonstrate that the adopted active disturbance rejection control scheme has good dynamic performance and uncertain disturbance robustness.